2020
DOI: 10.1016/j.jmii.2020.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic carrier state, acute respiratory disease, and pneumonia due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2): Facts and myths

Abstract: Hsueh P-R, Asymptomatic carrier state, acute respiratory disease, and pneumonia due to severe acute respiratory syndrome coronavirus 2 (SARSCoV-2): Facts and myths, Journal of Microbiology, Immunology and Infection, https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
736
5
65

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 852 publications
(824 citation statements)
references
References 42 publications
18
736
5
65
Order By: Relevance
“…Since the first reported case of coronavirus disease 2019 (COVID-19) in Wuhan, China at the end of 2019, COVID-19 has rapidly spread throughout China and also involved many other countries in spite of the global effort to prevent its spread. [1][2][3][4] According to the report of World Health Organization (WHO), COVID-19 has affected 84,503 patients in 57 countries/territories and caused 2,924 deaths by February 29, 2020, of which approximately 92.9% of cases and 97.1% of deaths are in China. 1 Among these 57 countries/territories, the cases reported in 20 countries/territories were attributed to local transmission of COVID-19, while those in 37 countries/regions were imported cases.…”
Section: Global Epidemiology Of Covid-19mentioning
confidence: 99%
“…Since the first reported case of coronavirus disease 2019 (COVID-19) in Wuhan, China at the end of 2019, COVID-19 has rapidly spread throughout China and also involved many other countries in spite of the global effort to prevent its spread. [1][2][3][4] According to the report of World Health Organization (WHO), COVID-19 has affected 84,503 patients in 57 countries/territories and caused 2,924 deaths by February 29, 2020, of which approximately 92.9% of cases and 97.1% of deaths are in China. 1 Among these 57 countries/territories, the cases reported in 20 countries/territories were attributed to local transmission of COVID-19, while those in 37 countries/regions were imported cases.…”
Section: Global Epidemiology Of Covid-19mentioning
confidence: 99%
“…Though Taiwan is very close to China geographically, there were much fewer confirmed COVID-19 infected patients in Taiwan, compared with many countries. 3,4 Since Taiwan is not a member of WHO, we receive a limited assistance from WHO. 5 However, the successful control programs for COVID-19 infection in Taiwan are promising and it may resulted from the experience of managing the outbreak of Severe Acute Response Syndrome(SARS) in Taiwan, 2003.…”
Section: Perspectivesmentioning
confidence: 99%
“…Several studies demonstrated the infection control policy of medical centers in Taiwan. 4,9,10 For different infectious diseases, the roles and infection control strategies in various levels of healthcare system would be different. The strategies of preventing COVID-19 in community hospitals have not been described.…”
Section: Perspectivesmentioning
confidence: 99%
“…En los casos más graves, la COVID-19 puede producir neumonía, que se puede complicar con un síndrome de disneas y shock distributivo, cardiogénico o mixto en los casos más graves. La población de edad avanzada y/o con comorbilidades médicas preexistentes son las más vulnerables y presentan con mayor frecuencia formas más graves de la enfermedad 8,9,[13][14][15][16] . En este hecho puede influir tanto el proceso de envejecimiento fisiológico como, especialmente, la mayor prevalencia en pacientes de edad avanzada de fragilidad y comorbilidades que contribuyen a una disminución de la reserva funcional, que a su vez reduce la capacidad intrínseca y la resiliencia y dificulta la lucha contra las enfermedades y las infecciones 16 .…”
Section: Manifestaciones Clínicas De La Covid-19 Y Peculiaridades Enunclassified